Bezpośrednie inwestycje zagraniczne w nowych państwach ASEAN: Kambodży, Laosie, Wietnamie (CLV) - Pietrasiak, Małgorzata (Foreign direct investment in the new members of the ASEAN: Cambodia, Laos, Vietnam (CLV), 2009)
Entering ASEAN association by Indo-Chinese countries: Vietnam (1995), Laos (1997), Cambodia (1999) enabled to raise a level of foreign direct investment (FDI). For those countries it was a huge chance to develop and to jo in integration processes of the region. Indochina countries have made an effort to create favourable climate for foreign investments. However, in each of those countries conditions of locating FDI differ. Among those three countries the most liberal conditions are offered by Cambodia, but Vietnam, due to political stability, its potential and international activity, attracts the greatest number of investors. At the beginning the majority of investments derived from countries in the region, foremost ASEAN countries. Currently the sources of capital are more diverted, which is particularly visible in Vietnam. Among three researched Indochina countries Cambodia (2004) and Vietnam (2007) are WTO members
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 295-306